Comparative effectiveness of horticultural therapy modalities for cognitive function and depressive symptoms in older adults with cognitive impairment: Protocol for a systematic review and network meta-analysis - Jingjing Yan; Weihua Li; Yingjie Shen; Qiyuan Lyu; Suwen Hu; Nan Xu (PLoS ONE, 2026)
Introduction Cognitive impairment in older adults is often accompanied by depressive symptoms, leading to reduced quality of life and increased risk of disability and mortality. Horticultural therapy has been increasingly used as a non-pharmacological intervention; however, its effectiveness may vary across different intervention modalities and delivery characteristics. Existing meta-analyses have primarily focused on overall effects and have not compared different horticultural therapy modalities. This study aims to evaluate and rank the comparative effectiveness of horticultural therapy delivered through different modalities using a network meta-analysis. Methods and analysis Randomized controlled trials (RCTs) involving older adults with cognitive impairment will be included. The intervention group will receive horticultural therapy in addition to routine care, while the control group will receive routine care alone. Eight databases (PubMed, Embase, the Cochrane Central Register of Controlled Trials (CENTRAL), Web of Science, CINAHL, PsycINFO, China National Knowledge Infrastructure (CNKI), and Wanfang Database) will be searched from inception to May 2026. Interventions will be classified based on delivery characteristics, including environmental settings, cultivation substrates, and levels of participant engagement. Primary outcomes are cognitive function and depressive symptoms. Two reviewers will independently perform study selection, data extraction, and risk of bias assessment using the Cochrane Risk of Bias 2 tool. Pairwise meta-analysis and frequentist network meta-analysis will be conducted using the R (package “netmeta”), and treatment rankings will be estimated using surface under the cumulative ranking curve (SUCRA) values. Ethics and dissemination Ethical approval is not required. Findings will be disseminated through a peer-reviewed publication. Trial registration PROSPERO registration number: CRD420251185714.